Rhetorical tools in a collection of poems Masih Ingatkah Kau Jalan Pulang by sapardi djoko damono and rintik sedu - Rr. Purwanti; Ratu Wardarita; Arif Ardiansyah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aims to analyze the form of rhetorical tools in a collection of poems Masih Ingatkah Kau Jalan Pulang by Sapardi Djoko Damono and Rintik Sedu. Data analysis was carried out in a descriptive-qualitative manner consisting of words, phrases, or sentences in poetry. The results of the research are in the form of rhetorical means, consisting of simile, metaphor, personification, and synecdoche display, repetition structure manipulation, parallelism, polysyndeton, asyndeton, hyperbole, rhetoric, and climax, as well as images of sight, hearing, smell, touch, and motion. The function of rhetoric means is to intensify, enliven, provide clarity of imaginary images, aesthetically, emphasize, rhetorically, generate more effective associations of meaning, make it concrete, and make it easier to imagine. The dominant use of rhetorical means, in structural manipulation, is parallelism and repetition, in images are images of motion, sight, and hearing, in a presentation are metaphors and personifications. The learning design in SMP must be student-centered, paying attention to individual differences and selecting the right learning model.